Internalization of the Values of the Prophet's Hadith in the Formation of Muslim Entrepreneurial Character - Yuniatul Jannah; Mohammad Fattah (Values: Jurnal Kajian Islam Multidisiplin, 2026)
This articel discusses the role of the Prophet Muhammad’s  hadith in shaping an entrepreneurial mindset based on Islamic values. Entrepreneurship in the Islamic perspective is not merely oriented toward economic profit but also emphasizes ethical, moral, and social responsibility aspects. This study employs a library research method by analyzing selected hadiths related to economic activities, such as honesty, hard work, independence, and trustworthiness. The findings indicate that hadith plays a significant role in developing the character of Muslim entrepreneurs with integrity and a strong orientation toward business sustainability and blessing. These values remain relevant in the context of contemporary entrepreneurship to support ethical and responsible business practices. Therefore, the internalization of hadith values can serve as a foundation for building an entrepreneurial mindset that is not only economically productive but also morally grounded and socially beneficial